Academic performance prediction algorithm based on fuzzy data mining - Anil Kumar Tiwari; G. Ramakrishna; Lokesh Kumar Sharma; Sunil Kumar Kashyap (IAES International Journal of Artificial Intelligence (IJ-AI), 2019)
This paper presents an algorithm for prediction of academic performance of students by fuzzy data mining. The fuzzy-trace concept applied to predict the academic performance of the students. An algorithm is proposed in this paper lies with this idea. The fuzzy academic set is generated from the student’s academic data. This is analyzed by the fuzzy-matrix set. The prediction academic data is referred as the management of data or data mining. Data mining is the science of analyzing the data for obtaining more information than Keywords the current information. The hidden information appears by this technique.